2016
DOI: 10.24195/2414-4665-2016-8-21
|View full text |Cite
|
Sign up to set email alerts
|

Specialized Training and Bioenergy State of Football Players With Different Typological Properties of the Higher Parts of the Nervous System

Abstract: Психологія - Психология -Psychology "Наука і освіта", №5, 2016 (самодостатньо-впевнений, цілеспрямовано-наполегливий, саморегулятивний, ініціативно-імпульсивний, рішуче-сміливий, пасивно-слабовольний), та розглянуто детермінанти розвитку вольових яко-стей.Ключові слова: воля, вольові якості, розвиток вольових якостей, вольові типи особистості, навчально-професійна діяльність.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
79
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(93 citation statements)
references
References 0 publications
3
79
0
8
Order By: Relevance
“…But at the time of the reaction to the visual and auditory stimuli are influenced by the factors of special training. Many researchers (Shumway-Cook, Woollacott, 1995, Lyzohub, Nechyporenko, Pustovalov, Suprunovych, 2016, Ilin, 1974 found that sports such as sports games (basketball, volleyball, football, etc. ), martial arts influence development psychophysiological functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But at the time of the reaction to the visual and auditory stimuli are influenced by the factors of special training. Many researchers (Shumway-Cook, Woollacott, 1995, Lyzohub, Nechyporenko, Pustovalov, Suprunovych, 2016, Ilin, 1974 found that sports such as sports games (basketball, volleyball, football, etc. ), martial arts influence development psychophysiological functions.…”
Section: Introductionmentioning
confidence: 99%
“…Notes: 1 -time of the latent period of a simple visual-motor reaction (ms); 2 -time of the latent period of the reaction of selecting 2 objects from 3 (ms); 3 -time of the latent period of the reaction of selecting 2 objects from 3 in the feedback mode (ms); 4 -the minimum signal exposure time in the test with feedback (ms); 5 -total test time with feedback (ms); 6 -time to reach the minimum signal exposure in a test with feedback (ms); 7 -work time on the second However, in the age group of 15-16 years, a change in the quantity and quality of the interrelations studied during 3 months of training is more pronounced than in the age group of 12-13 years. This may be due to the age characteristics of young football players, since in 15-16 years there is some mismatch in the interaction of various functions due to puberty, the change in psychophysiological functions occurs faster than in older ones (Lyzohub, Nechyporenko, Pustovalov, Suprunovych, 2016).…”
mentioning
confidence: 99%
“…Mental chronometry is one of the main paradigms of experimental and cognitive psychology and has found its place in Physiother Quart 2018, 26 (4) physiotherapyquarterly.pl various disciplines, including cognitive psychophysiology, cognitive neuroscience, and behavioural neuroscience, in order to identify the mechanisms underlying cognitive processing [10][11][12]. Mental chronometry is studied with the measurement of reaction time, which is the time elapsed between the presentation of a sensory stimulus and the subsequent behavioural response [13][14][15]. The reaction time is limited not only by the signal transmission rate in the white matter, but also by the properties of synaptic and neuronal processing in cortical grey matter [16].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the research focuses on the reaction time. There are several methods of measurement: the time of a simple reaction, the time of a complex reaction, the reaction time to a moving object, and others [12,13,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation